Green architecture in the Republic of Tatarstan: the case of Kazan - Zakirova Tatyana R. (Архитектон)
The article reviews the development of green architecture in Tatarstan from the first environmentally friendly technologies to modern innovative projects using Kazan as an example. The role of state support, regulatory documents, programs and local community engagement in the implementation of environmental projects are considered. Kazan became the vanguard of the "green" movement in Russia from its beginning, and the first energy-efficient house in Russia was built in Kazan. Currently Tatarstan is a leader in green technologies. The application of energy-efficient solutions reduces energy consumption and improves microclimates while the use of local materials reduces the carbon footprint and supports the economy. The study demonstrates that green architecture improves the quality of the urban environment and life, creating conditions for sustainable development of the region. Particular attention is paid to educational programs and the popularization of green technologies among the general population, which is a key factor for further success in this area.